2017
DOI: 10.1638/2016-0256.1
|View full text |Cite
|
Sign up to set email alerts
|

OCULAR FINDINGS AND SELECT OPHTHALMIC DIAGNOSTIC TESTS IN CAPTIVE AMERICAN WHITE PELICANS (PELECANUS ERYTHRORHYNCHOS)

Abstract: The aim of this study was to establish normal ophthalmic parameters for select diagnostic tests in American white pelicans (Pelecanuserythrorhynchos). Twenty-one zoo-housed American white pelicans were manually restrained for noninvasive ocular diagnostic testing and complete ophthalmic examination. Tear production quantification using the phenol red thread test (PRTT), fluorescein staining, and intraocular pressure (IOP) evaluation were performed. In addition, conjunctival aerobic bacterial culture and cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…Given that there is an inter-specific difference in normal tear production in birds, reference values for each species need to be established (Table 5) [8][9][10][18][19][20][21][22][23]25,26,29,[34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that there is an inter-specific difference in normal tear production in birds, reference values for each species need to be established (Table 5) [8][9][10][18][19][20][21][22][23]25,26,29,[34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Fornazari et al (2018) examined two populations of two differently aged chickens (5 and 42-day-old chicks), and they also reported that tear production increases with age [29]. American white pelicans (Pelecanus erythrorhynchos) 14.9 ± 7.84 mm/15 s PRTT 6 [44] Atlantic puffins (Fratercula arctica) OD 1 : 7.5 mm/15 s (IQR 13 : 6.5-9.3) OS 2 : 5.0 mm/15 s. (IQR 13 : 4.0-7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterochromia iridis, in which the two irises of a single individual are different colors, has also been reported in several species of birds but seems to be uncommon (Poor 1946, Ryan 2013, David et al 2013, Ruiz-Esparza et al 2017, Kinney et al 2017). However, a study of Common Cuckoos (Cuculus canorus) found a consistent tendency for the left eye to have more extensive dark flecking than the right eye (Yoo et al 2017) -although the mechanism and significance of this tendency is unknown -and few studies have sought to quantify these types of differences.…”
Section: Variation In Eye Color Within Speciesmentioning
confidence: 98%